Optimalisasi Pemberdayaan Ekonomi Pesantren melalui Pengembangan Keterampilan Kreatif - Ahmad Syathiri; Fera Widyanata; Farida Kumalasari; Yulia Hamdaini Putri; Heru Wahyudi (Penerbit Goodwood, 2026)
Purpose: This community service initiative aimed to empower female students at SMA IT Raudhatul Ulum in Desa Sakatiga through entrepreneurship training and practical workshops on handmade accessory creation. The program, conducted by faculty and students from Universitas Sriwijaya, focused on equipping participants with essential entrepreneurial knowledge, including business concepts, marketing strategies, and financial management. Research Methodology: The methodology involved interactive discussions and hands-on practice, allowing students to engage actively in the learning process. Result: Results indicated a significant improvement in the participants' understanding of entrepreneurship, fostering confidence in their ability to start or develop their own businesses. Conclusions: This training can enhance participants' creative, technical, and social skills while also fostering entrepreneurial interest and equipping participants with important soft skills for the future. Limitations: However, the program faced limitations, such as time constraints and varying levels of prior knowledge among participants, which could affect the overall effectiveness of learning. Contributions: Nonetheless, the contributions of this initiative are noteworthy, as it not only enhanced the participants' technical skills but also promoted creativity and collaboration, ultimately strengthening the entrepreneurial ecosystem within the community. This initiative exemplifies the potential of educational institutions to play a pivotal role in economic empowerment and community development through targeted skill-building programs.